Medication non-adherence: reflecting on two decades since WHO adherence report and setting goals for the next twenty years - Kardas, Przemyslaw; Bennett, Bryan; Borah, Bijan; Burnier, Michel; Daly, Christopher; Hiligsmann, Mickael; Menditto, Enrica; Peterson, Andrew M.; Slejko, Julia F.; Tóth, Krisztina; Unni, Elizabeth; Ágh, Tamás (Frontiers in Pharmacology, 2024)
BackgroundNon-adherence to medication remains a persistent and significant challenge, with profound implications for patient outcomes and the long-term sustainability of healthcare systems. Two decades ago, the World Health Organization (WHO) dedicated its seminal report to adherence to long-term therapies, catalysing notable changes that advanced both research and practice in medication adherence. The aim of this paper was to identify the most important progress made over the last 2 decades in medication adherence management and to initiate a discussion on future objectives, suggesting priority targets for the next 20 years.MethodsThis research used the WHO adherence model as a theoretical framework, categorizing adherence factors into five dimensions: health system, therapy, condition, patient-related, and socioeconomic. Ten international experts, five from Europe and five from the United States, were assigned to these dimensions and participated in structured online discussions. Initially, based on their desk reviews, experts identified significant achievements and future targets. They then ranked these items and provided feedback through several rounds, ensuring anonymity to minimize bias, ultimately reaching a consensus. This iterative process allowed for the creation of top-ten lists of past achievements and future targets for medication adherence management over the next 20 years.ResultsAnalysis of the top-ranked achievements affirms that notable progress has been made in medication adherence research and practice over the past 20 years, with increased awareness and a surge in dedicated scientific publications. Despite these advancements, non-adherence remains a prevalent issue, underscoring the need for the ongoing implementation of innovative solutions identified in this work, such as novel digital health solutions. Interdisciplinary collaboration and a holistic understanding of patient behaviours and socio-economic factors are crucial.ConclusionWhile refraining from imposing a rigid “adherence Decalogue,” we are confident that this overview of recent achievements and the curated selection of future targets may provide a useful foundation for further discussions aimed at advancing medication adherence management. Our results call for a paradigm shift, advocating the repositioning of medication adherence on national agendas and underscoring the necessity for an adherence-supportive ecosystem that extends beyond mere patient support.